A Review on Phytoconstituents for the Treatment of Psoriasis - Aneja, Simran; Mittal, Arun; Dhiman, Neerupma; Agarwal, Gaurav (Pharmacognosy Reviews)
Psoriasis once thought to be largely an epidermal keratinocyte problem, it is now understood that it is a disorder due to immune-mediation. Skin hyperplasia of vascular hyperplasia, epidermal keratinocytes, and permeation of neutrophils, leucocytes, and extra types of T lymphocytes in affected skin. The pathophysiology of the illness is intricate and includes both genetic and cellular elements. As a result, there are many different therapeutic approaches that work on various targets, ranging from symptomatic treatment to immune system modulation. Drugs are known to cause the condition but the precise cause of it is uncertain. Environmental factors like smoking, infections and seasonal changes are also responsible. Natural alternatives are being sought after due to the harmful impact on life quality and dangerous adverse effects of conventional treatment. There are a variety of plants that have been utilized in conventional psoriasis treatment methods that could serve as safer substitutes. The emphasis of the current review article is on pharmacological studies of anti-psoriatic plant, plant extracts, and formulation. The review has also taken into account several chemical elements extracted from plants that are accountable for antipsoriatic activity and their mechanisms of action. This review is necessary to choose these plants for more research in order to identify the chemical components that fight psoriasis and determine how they work.
Keywords: Phytoconstituents; Psoriasis; Anti-psoriatic plants; Pharmacological studies